Depression of corticomotor excitability after muscle fatigue induced by electrical stimulation and voluntary contraction - Kotan, Shinichi; Kojima, Sho; Miyaguchi, Shota; Sugawara, Kazuhiro; Onishi, Hideaki (Frontiers in Human Neuroscience, 2015)
In this study, we examined the effect of muscle fatigue induced by tetanic electrical stimulation (ES) and submaximal isometric contraction on corticomotor excitability. Experiments were performed in a cross-over design. Motor-evoked potentials (MEPs) were elicited by transcranial magnetic stimulation (TMS). Corticomotor excitability was recorded before and after thumb opposition muscle fatigue tasks, in which 10% of the maximal tension intensity was induced by tetanic ES or voluntary contraction (VC). The participants were 10 healthy individuals who performed each task for 10 min. Surface electrodes placed over the abductor pollicis brevis (APB) muscle recorded MEPs. F- and M-waves were elicited from APB by supramaximal ES of the median nerve. After the tetanic ES- and VC tasks, MEP amplitudes were significantly lower than before the task. However, F- and M-wave amplitudes remained unchanged. These findings suggest that corticospinal excitability is reduced by muscle fatigue as a result of intracortical inhibitory mechanisms. Our results also suggest that corticomotor excitability is reduced by muscle fatigue caused by both VC and tetanic ES.